High‐flux ptychographic imaging using the new 55 µm‐pixel detector `Lambda' based on the Medipix3 readout chip. Issue 6 (14th September 2014) - Wilke, R. N.; Wallentin, J.; Osterhoff, M.; Pennicard, D.; Zozulya, A.; Sprung, M.; Salditt, T.
<x xml:space="preserve">Abstract</x> Suitable detection systems that are capable of recording high photon count rates with single‐photon detection are instrumental for coherent X‐ray imaging. The new single‐photon‐counting pixel detector `Lambda' has been tested in a ptychographic imaging experiment on solar‐cell nanowires using Kirkpatrick–Baez‐focused 13.8 keV X‐rays. Taking advantage of the high count rate of the Lambda and dynamic range expansion by the semi‐transparent central stop, a high‐dynamic‐range diffraction signal covering more than seven orders of magnitude has been recorded, which corresponds to a photon flux density of about 105 photons nm−2 s−1 or a flux of ∼1010 photons s−1 on the sample. By comparison with data taken without the semi‐transparent central stop, an increase in resolution by a factor of 3–4 is determined: from about 125 nm to about 38 nm for the nanowire and from about 83 nm to about 21 nm for the illuminating wavefield.